Musical proportions in a Jewish portable sanctuary - Debevec, Leon (Edinost in dialog, 2025)
An architectural reading of biblical texts about the Jewish portable sanctuary, especially the metrical properties of its components, shows the presence of relationships that belong to the family of musical proportions. This paper discusses the question of whether the understood proportions are merely concealed in the dimensional characteristics of the elements of this composite architecture, or whether they are in fact part of its deep structure. The discussion shows that the musical proportions are not just some sort of by-product or curiosity of the defined measurements of the most important parts of the Jewish portable sanctuary, but rather they regulate almost all of its essential design features in a mutual balance.
Keywords: architecture; arhitektura; compositional analysis; glasbene proporcije; kompozicijska analiza; musical proportions; sveti šotor; tabernacle